A national health service : draft memorandum on the government's proposals
1944-04-14 1944 1940s 14 pages - 3 - 6. - Regional Hospitals Councils. It is clear that no adequate and efficient planning of National Service is possible if the relatively small areas of the Joint Authorities are to be regarded as water-tight compartments, and if the only machinery for securing co-ordination of their work is to be found in a central body in London. If the standard of the hospital service of the country is to be raised, it is vital that backward hospitals, both voluntary and local authority, should be brought into close and regular contact with the leading centres of medical knowledge which are to be found in the university cities. A regional council affords the only effective means of establishing such contact. Occasional meetings will not alone achieve this object. To ensure that there is adequate linkage between the areas, they must be appropriately grouped regions, and in each region there must be established a Regional Hospitals Council. These councils must be statutory bodies, charged with the duty of considering and adjudicating upon the plans of the several areas, with a view to ensuring the co-ordination of the hospital services throughout the region. The schemes forwarded by the several areas would be correlated by the Regional Hospitals Council into a general regional plan. If, in the opinion of the Council, the scheme submitted by any area required modificaion or alteration, it would be referred back to the area concerned for further consideraion. The Regional Council would forward the regional plan, when agreed, direct to the Minister, who would be under obligation to consult the Central Hospitals Board before giving it his approval. The Regional Hospitals Councils would be mainly composed of representatives, both lay and medical, of the voluntary hospitals and of the joint authorities of the region, in equal numbers, with an independent chairman appointed by the Minister of Health. The members would be appointed by the bodies they represent, and must be persons with a practical knowledge and experience of hospital work. It is regarded by the voluntary hospitals as the greatest importance, if the standard of hospital service is to be raised, that, as far as possible, each region should include at least one university teaching school, and that representatives of the universities should be appointed to the Regional Hospitals Councils. 7. - Local Hospitals Councils. Since, also, the proposed Local Health Services Councils, like the Central Health Services would be concerned with all aspects of the service, it is vital to the efficiency of the hospital side that in each Joint Authority area there should be, as at the centre, a Local Hospitals Council composed primarily of representatives of the local authority and voluntary hospitals in equal numbers, together with representatives of the local consultant service, with an independent chairman appointed by the Minister. These Local Hospitals Councils should be statutory bodies, charged with the duty of preparing plans for the area hospital service, and advising on all matters which appertain to the maintenance and efficiency of the service as a whole. It is fundamental to the whole conception of partnership upon which the proposals of the government are based that the responsibility for the planning of the service should be entrusted at each stage to a body upon which the voluntary hospitals are properly represented. The area hospital plan, prepared by the Local Hospitals Council would be forwarded to the Joint Authority*, who, in turn, would forward it to the Regional Hospitals Council for approval. Whilst the Joint Authority would be under an obligation to forward the plan as submitted, they would be at liberty to comment on it to the Regional Council, if they so desired. (contd.) 292/847/2/33